Utilizing Social Reality Videos in Mobile Apps to Enhance Electronic Learning: Examining the Influence on Cognitive Learning Outcomes Among Students - Yazidi, Rachid El (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2023)
This research endeavors to evaluate the effectiveness of incorporating electronic learning (e-learning) with social reality videos into a mobile application to enhance students' cognitive learning outcomes. The study adopts an experimental design, specifically a pretest-posttest control group design, involving two distinct groups: the experimental group exposed to e-learning featuring social reality videos, and the control group engaged in traditional face-to-face learning utilizing the expository method. Each group comprised twenty-eight students, and both groups underwent pre-tests and post-tests with identical tasks. The primary focus of this investigation is the assessment of cognitive learning outcomes among students, representing the educational impact of induced learning within each treatment group. Analysis of students' learning outcomes includes descriptive methods (such as the average learning outcomes and n-gain) and statistical procedures, including hypothesis testing to determine differences in achievement between the treatment groups, conducted at a significance level of 0.05. In summary, the findings of this study reveal that the integration of e-learning with social reality videos significantly enhances students' learning outcomes, surpassing the effectiveness of the expository method. Consequently, the researchers recommend the simultaneous incorporation of this innovative approach into conventional classroom lectures.